Keefektifan Kegiatan Bongkar Muatan General Cargo Pt. Atho Tama di Pelabuhan Tanjung Priok Jakarta - Himawan Aditya Pratama; Robinsar Yuliando (Sekolah Tinggi Maritim Yogyakarta, 2021)
There are five main components that affect port performance, namely: Ship movement, labor productivity, equipment, cargo intensity at moorings, and cargo flow intensity at storage locations. (media.neliti.com, 2019). These five components affect the effectiveness of loading and unloading activities at the port. In analyzing the data the author uses qualitative methods in analyzing a data that is in the field. Factors that greatly affect delays or hinder unloading activities are when the process of unloading cargo; the ship performs ballast; bad weather. General Cargo's unloading process performs with cargo safety guidelines, which prioritize safety in loading and unloading performance, namely to cargo. Every ship is more concerned with work safety, but on the other hand, the ship is more concerned with cargo safety when operating the unloading to the dock or to the barge.